Prognostic Model to Identify Patients With Myelofibrosis at the Highest Risk of Transformation to Acute Myeloid Leukemia - Quintás-Cardama, Alfonso (2013)
A fraction of patients with myelofibrosis (MF) will progress to acute myeloid leukemia (AML) but no current tools are available to identify such patients. By multivariate analysis of 649 patients with MF, we have identified several independent prognostic factors for death. Among those factors, the presence of bone marrow blasts >10% and high risk karyotype were identified as independent risk factors for transformation from MF to AML. BACKGROUND: Some patients with myelofibrosis (MF) progress to acute myeloid leukemia (AML). Current prognostic tools were not devised to assess risk of AML transformation. METHODS: Multivariate analysis in 649 patients followed for a median of 19 months (range, 1-180 months). RESULTS: We identified age > 60 (P = .004; hazard ratio [HR], 1.63), platelets <100 × 10(9)/L (P < .001; HR, 1.62), bone marrow blast > 10% (P = .002; HR, 2.18), high-risk karyotype (P < .001; HR, 2.44), transfusion dependency (P < .001; HR, 2.64), performance status > 1 (P = .003; HR, 1.47), lactate dehydrogenase > 2000 U/L (P < .001; HR, 1.62), previous hydroxyurea (P < .001; HR, 1.69), and male sex (P = .005; HR, 1.41) as independent poor prognostic factors for survival. Using the same baseline variables we identified bone marrow blasts >10% and worst karyotype as independent risk factors for AML transformation. Patients with 1 or both of these risk factors (n = 80; 12%) had a median survival of 10 months and a 1-year AML transformation rate of 13% (2% if none of those factors, P = .001). CONCLUSION: We have identified risk factors that predict high risk of transformation from MF to AML.